Submerged Economies in Colombia and their Link to Social Representations of Work. A Study from the Perspective of Social Psychology - Omar Cabrales Salazar; Jorge Antonio Bermúdez Mejía; Vianney Rocío Díaz Pérez (Eleuthera, 2023)
This reflection article aims at exploring the bases of the historical construction of work in Colombia, its social representations, and its incidence on the constitution of submerged economies such as illegal drug trafficking. The historical method of consulting secondary sources that testify to the behavior of Colombian society at the end of the Colony and in the Republican period is used in order to connect the historical scenarios with the present. Reference is made to the path of dependence, the critical theory of colonialism and social representations of work. The results show that social psychology and social representations of work have consequences in the creation and maturation of informal economies and in the tendency to get rich quickly and easily in some sectors of the Colombian society. In conclusion, these contexts end up being consolidated as the basis of an illegal ‘industry’ that constantly reinvents itself and gives rise to the development of certain skills useful to survive in an unequal and violent context materialized in the so-called drug trafficking era, which began in the 1970s.